(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
The research aimed to explore the reality of organizational intelligence and its dimensions — namely (environmental understanding, collective intelligence, and strategic vision) — as well as sustainable development and its dimensions (economic, environmental, and social). The focus was on Al-Ittihad Food Industries Company. The research also sought to identify the correlation between organizational intelligence and sustainable marketing within the company. A descriptive approach was adopted, and the study sample consisted of 99 employees from various departments of the company. A questionnaire was designed as the main tool for data collection, in addition to conducting some personal interviews. Data were analyzed using SPSS software and Cronbach’s Alpha for reliability testing. The questionnaire relied on a five-point Likert scale. The research arrived at several key findings, most notably: The level of organizational intelligence and sustainable marketing practices in the company was moderate, There is a strong positive correlation between the dimensions of organizational intelligence and those of sustainable marketing, The results indicated that the t-test values were statistically significant for all research variables at a significance level of (α ≤ 0.05), confirming a meaningful and positive correlation between organizational intelligence and sustainable marketing. The study recommended that Al-Ittihad Food Industries Company should place greater emphasis on continuous learning and the need to clarify visions, plans, and future directions with its employees.